Gambaran Pola Makan pada Pasien Diabetes Mellitus Tipe 2 di RSUD dr. Slamet Garut - Bambang Aditya Nugraha; Sulastini Sulastini (Jurnal Medika Cendikia, 2022)
Diabetes Mellitus (DM), especially type 2 is a chronic disease whose prevalence is increasing. One of the factors causing the high number of patients with type 2 DM is irregular eating patterns with high calorie intake from carbohydrates and fats. Slamet Garut. The research method used is descriptive, with a purposive sampling technique, the number of samples is 97 respondents with the criteria of patients diagnosed with DM more than 6 months, not having complications. The data collection technique was done by using a questionnaire. The results of the study and the conclusion that the diet based on the type of food consumed by more than half of the respondents was irregular, the eating pattern based on the amount of food consumed by the majority of the respondents was irregular and the eating pattern of the patients was based on an irregular eating schedule. It is recommended that nurses collaborate to provide nutritional counseling, vitamins or nutrition in carrying out diets or eating patterns.